A 195Pt NMR study on zero-magnetic-field splitting and the phosphorescence properties in the excited triplet states of cyclometalated platinum(ii) complexes. Issue 19 (29th April 2020) - Akagi, Soichiro; Fujii, Sho; Kitamura, Noboru
Abstract : The strength of zero-magnetic-field splitting in the excited triplet states of metal complexes is reflected in the metal NMR chemical shifts. Abstract : We report the factors governing zero-magnetic-field splitting (zfs) in the lowest-energy electronically excited triplet (T1 ) states of cyclometalated platinum(ii ) complexes, whose zfs energies between the lowest- ( φ 1 ) and highest-energy spin-sublevels ( φ 3 ) in the T1 states (Δ E zfs ) are already known: [Pt(bhq)(dpm)] (1Pt ), [Pt(thpy)(acac)] (2Pt ), [Pt(ppy)(acac)] (3Pt ), cis -[Pt(thpy)2 (4Pt ), and cis -[Pt(ppy)2 ] (5Pt ), where bhq, dpm, thpy, acac, and ppy are benzo[ h ]quinoline, dipivaloylmethane, 2-(2-thienyl)pyridine, acetylacetone, and 2-phenylpyridine, respectively. As one of the important findings, we show the relationship between the Δ E zfs and 195 Pt NMR chemical shifts of the five Pt(ii ) complexes. The implications of the Δ E zfs values on the emission properties of the Pt(ii ) complexes in acetonitrile at 293 K are also discussed. In particular, we demonstrate that the radiative rate constants of the Pt(ii ) complexes correlate with both Δ E zfs and 195 Pt NMR chemical shifts.